Epidemiology of chronic and acute pancreatitis in India (EPICAP-India): protocol for a multicentre study - Sanjeev Kumar; Saransh Jain; Vineet Ahuja; Rakesh Kumar; Anand Krishnan; Pankaj Bhardwaj; Shalimar; Nitya Wadhwa; Ashish Agarwal; Deepak Gunjan; Sudipta Dhar Chowdhury; Anoop Saraya; et al. (BMJ Open Gastroenterology)
Introduction Acute and chronic pancreatitis (CP) are inflammatory conditions of the pancreas that cause local and systemic complications. The epidemiology of these conditions are not well-known in India.Methods and analysis We describe the protocol and procedures of a multicentre study for delineating the epidemiology of pancreatitis in India. We plan to cover 110 000 people across 10 geographically distributed sites in 10 states of India to estimate the burden and risk factors of CP. Trained investigators will make house visits and screen for abdominal pain requiring hospitalisation or pre-diagnosed CP. The screened positive participants will be reviewed by a gastroenterologist to confirm the diagnosis of CP based on radiological imaging. For each case, four controls will be selected and data on risk factors for CP (tobacco, alcohol, family history, metabolic causes) and blood for genetic markers will be collected. Information on the cost of treatment and quality of life will be collected from patients with CP. For estimating incidence of acute pancreatitis (AP), hospital-based sentinel surveillance will be conducted in 10 districts across these 10 states. All hospitals in the district will be contacted to provide a line list of admissions due to acute abdomen including AP for 2 years. The spread of acute abdomen cases will be used to define the catchment area and estimate the denominator population. The line-listed cases with AP living in the catchment area will form the numerator to calculate the incidence. The study will provide critical information for planning pancreatitis-related services in the country.Ethics and dissemination The institutional ethics committee (IECs) at all the participating sites have given their approval for the study. All the participants whose data will be collected will be included after written informed consent. The results may be presented at national or international conferences and will be reported in peer-reviewed publications.